Social Media Use and Perceived Self-Efficacy of Adolescents from Government and Private Schools - Singh, Priyanka; Kewalramani, Soni; Chandra, Ritu (Journal of Neonatal Surgery, 2025)
This quantitative study has been done on the 400(N) adolescents of Lucknow. The objective of present study is to see the role of patterns of social media use on perceived self-efficacy of adolescents. The data was collected by offline mode on students of aged from 12 to 18. Standard questionnaire is used for data collection. Mean analysis and T test is used for analysis. In result, it is found that patterns of social media have significant impact perceived self-efficacy of adolescents.